Fenomena Keterbukaan Diri Selebgram Perempuan di Kota Medan Sebagai Cermin Budaya Populer di Media Sosial Instagram - Yolanda Harahap; Rahmanita Ginting; Leylia Khairani (Universitas Medan Area, 2021)
This research aims to analyse the phenomenon of self-disclosure and determine the type of self-disclosure of female Instagram celebrities in Medan as popular culture on Instagram social media. This research uses Self Disclosure Theory and New Media Theory. This research method with qualitative approach. This research uses in-depth interview and observation data collection techniques. Informants in this study were five female Instagram celebrities in Medan, who were selected according to the criteria of the research informant until the information was at its saturation point. The results obtained from this study are female Instagram celebrities in Medan discovering a new perspective on themselves by opening themselves up through the Insta Story feature on Instagram social media, self-disclosure is a job desk for Instagram female Instagram celebrities in Medan, they have pioneered in the trend of opening themselves through the Instagram insta story feature, they are making the pioneers as an example and reference for acting on Instagram social media. The female Instagram celebrities in Medan more often share daily moments than their opinions on updating issues. The moment is about their work or college, a moment of social activity, a moment of hangout, and a vacation moment.